2018
DOI: 10.3390/cells7120279
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in Proteostasis: Friend and Foe in Cardiac Diseases

Abstract: Due to ageing of the population, the incidence of cardiovascular diseases will increase in the coming years, constituting a substantial burden on health care systems. In particular, atrial fibrillation (AF) is approaching epidemic proportions. It has been identified that the derailment of proteostasis, which is characterized by the loss of homeostasis in protein biosynthesis, folding, trafficking, and clearance by protein degradation systems such as autophagy, underlies the development of common cardiac diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…The underlying activation of autophagy could alleviate cardiac dysfunction and fibrosis induced by TAC or pressure overload. 4,9,[28][29][30] A multitude of epidemiological and experimental studies suggested that exercise contributed to physiological cardiac hypertrophy and attenuated pathological hypertrophy induced by various heart diseases, including myocardial infarction, heart failure, and cardiomyopathy. 31,32) Some further studies were conducted to illuminate the potential mechanism of exercise-induced cardioprotec-tion, and the results suggested that exercise prevented fibrosis, pro-inflammatory cytokines, oxidative stress, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying activation of autophagy could alleviate cardiac dysfunction and fibrosis induced by TAC or pressure overload. 4,9,[28][29][30] A multitude of epidemiological and experimental studies suggested that exercise contributed to physiological cardiac hypertrophy and attenuated pathological hypertrophy induced by various heart diseases, including myocardial infarction, heart failure, and cardiomyopathy. 31,32) Some further studies were conducted to illuminate the potential mechanism of exercise-induced cardioprotec-tion, and the results suggested that exercise prevented fibrosis, pro-inflammatory cytokines, oxidative stress, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, plenty of evidence indicates that cardiac autophagy is an underlying element for preserving cardiac function and protecting heart over hypoxia and LVH-induced cardiac dysfunction. [2][3][4] Therefore, it may be reasonable to hypothesize that exercise exerts a novel cardioprotective role through the mediation of autophagy signaling in the heart. Recent studies have shown that autophagy is involved in exercise-induced cardioprotection due to the upregulation of autophagy in both acute and endurance exercise.…”
mentioning
confidence: 99%
“…including the ubiquitin-proteasomal system (UPS) and autophagy [9]. In general, cellular stress, including stress caused by cardiac disease, activates multiple stress pathways, including the cytosolic heat shock response, the endoplasmic reticulum (ER) unfolded protein response (UPR ER ), and the mitochondrial UPR (UPR mt ) [10][11][12].…”
Section: Of 15mentioning
confidence: 99%
“…mTORC1 is a serine/threonine kinase and negatively regulates autophagy. 20,43,44 AMPK is responsible for sensing energy and nutrients and positively promotes autophagy by inhibiting mTORC1 or by phosphorylating Ulk1 at serine 313 and 777 and dissociating Ulk1 from mTORC1. 19,45,46 In this study, we found that Flt3 activation remarkably reduced Ang II-induced elevation of AMPK phosphorylation and the decrease of mTORC1 phosphorylation, resulting in the inactivation of autophagy ( Figure 6A,B).…”
Section: F I G U R Ementioning
confidence: 99%